Voting behaviour in the European Parliament 2009-2014: Implications for EU and national politics - Christine Nissen (Danish Institute for International Studies (DIIS), 2014)
The next European Parliament elections that take place from 22 to 25 May 2014 will not only shape politics in the European Parliament, but also influence the direction of the EU and Europe for the years to come. With the increased powers that the European Parliament gained after the entry into force of the Lisbon Treaty in 2009, the new political majority following the elections has the competences to change or block almost all EU policies as the main legislator in the EU in cooperation with the Council of Ministers. Besides its significantly expanded competences in legislation, the next European Parliament will also for the first time formally 'elect' the next President of the European Commission. [...]
Keywords: 300